BEYOND BCG - Usman, Javaid (Pakistan Armed Forces Medical Journal, 2022)
Easier said than done, tuberculosis (TB) is a preven-table and curable disease. The main key steps for the prevention of TB are to minimize transmission by early diagnosis, reduce infection translating into the disease by treating the latent tuberculosis infection and improve immunity through vaccination. Humanity in general and the medical community, in particular, can never thank enough the two French scientists, Albert Calmette (1863-1933) and his junior colleague Camille Guerin (1872-1961), for developing the BCG (Bacille Calmette Guerin) vaccine. Preparing the vaccine was by no means an easy task as it took the relentless effort of almost eleven years, continued even during the difficult circumstances of world war I, to attenuate a strain of Mycobacterium Bovis through 230 subcultures before putting it for use in humans in 1921.